Transformasi Pemikiran Pembaharuan Islam di Indonesia Abad 20 (Pemikiran KH. Abdurrahman Wahid Tahun 1970–2001) - Hambaliana, Dandie; Alfahmi, Ibrahim Nasrul Haq; Suprianto, Sopian; Nurcahya, Yan; Samsudin, Samsudin; Sudana, Djojo sukardjo (UNIVERSITAS SERAMBI MEKKAH, 2025)
The study of the transformation of Islamic thought in Indonesia is very important to see the connection between the Middle East and Indonesia. The discourse of Islamic renewal developed along with the complexity of the conditions in the Middle East, as well as the strengthening of the practice of purifying Islam and western modernism in the late 19th and early 20th centuries. KH. Abdurrahman Wahid is one of the many figures who contributed his thoughts in transforming Islam into Indonesian cultural values. Related to this, this study tries to look at the Islamic thoughts of KH. Abdurrahman Wahud in the late 20th century. In a work, namely Cosmopolitan Islam (Indonesian Values ​​and Cultural Transformation), he presents Islam as a religion that gives freedom to everyone to work without being limited by anything, such as political and ethnic identity. In this study, the author uses a historical research method consisting of four stages, namely Heuristics, Criticism, Interpretation, Historiography. Thus, this study will focus on the thoughts of KH. Abdurrahman Wahid in the renewal of Indonesian Islam. The results of this study indicate that the thoughts of KH. Abdurrahman Wahid has a close relationship with Islam from three dimensions. The first is in terms of Islamic Theology, Second is Islamic Mysticism and the last is Islamic philosophy. With these three parts, KH. Abdurrahman Wahid believes that Islam will reach its highest point of progress when all expressions and works of individual and group creations are given the same right to life, no matter how deviant or considered heretical. After studying the thoughts of KH. Abdurrahman Wahid, it appears that when choosing Islam as a basis, whatever path is chosen, as long as the foundation of Islam has been firmly embedded, then it will not be a problem. In other words, KH. Abdurrahman Wahid teaches us as Muslims to have an open mind, as well as broad insight.